PELATIHAN DAN PENDAMPINGAN PENGEMBANGAN HIDAYATULLAH TAHFIDZ GLOBAL ISLAMIC SCHOOLS - Supriyono Supriyono; Bahrul Ulum (Universitas Merdeka Madiun, 2022)
Abstract– This social service was based on the need assessment of the Hidayatullah Masjid Foundation for developing Hidayatullah Tahfidz Global Islamic Schools. This training was aimed at giving strategic management knowledge enhancement and capacity building for the so-called dewan Asatidz and Asatidziah or Islamic teachers of Play Group, Raudhlatul Atfal (Kindergarten), Madrasah Ibtidaiyah (Islamic Primary School), and Madrasah Tsanawiyah (Islamic Middle School). The training materials consisted of sector analysis, vision and mission unification, milestone, and implementation strategies and control. This training involved focus-grouped discussion, classical training, mentoring, and academic consultation. This training was evaluated by using 4 levels of Kirk Patrick assessment. Results of this training showed that the increase in the participants’ knowledge level reached 53.30%, and the perceptions of materials suitability, trainer performance, committee performance, and facilities are positive. Results of The evaluation showed that the participants had strong commitments to implement the training results. The participants had strong beliefs about the positive impact of the training on individuals, madrasah institutions, and the Hidayatullah Masjid Foundation. There needs improvement of time management for the next training. It is advised that this training is followed up by research and further training.